Sustainability Analysis of the Stunting Reduction Acceleration Program in Kubu Raya Regency - Resky Nanda Pranaka; Evi Gusmayanti; Indah Budiastutik; Malik Saepudin; Havid Aqoma (Window of Health : Jurnal Kesehatan, 2025)
Presidential Regulation Number 72 of 2021 on the Acceleration of Stunting Reduction sets a national target of reducing stunting prevalence to 14% by 2024 through integrated programs across government levels, from ministries to villages. In line with this policy, Kubu Raya Regency has shown a decline in stunting rates from 7.9% to 6.8% based on e-PPGBM data, indicating improved implementation of stunting reduction programs. This study aims to analyze the sustainability status of the stunting reduction program in Kubu Raya Regency using the Rapfish (Rapid Appraisal for Fisheries) multidimensional scaling approach. Data were collected from ten Regional Apparatus Organizations (OPDs) through surveys and interviews. The analysis involved six stages: identifying dimension characteristics, scoring on an ordinal scale, determining sustainability status, conducting sustainability checks, performing a sensitivity analysis, and applying a Monte Carlo simulation to account for uncertainty. The results show that the social and economic dimensions are categorized as "quite sustainable" with scores of 60.04 and 51.86, respectively, while the environmental dimension is "less sustainable" with a score of 38.02. Key attributes influencing sustainability include increasing the number of Open Defecation Free (ODF) villages, improving the accuracy of beneficiary data for food assistance, monitoring fortified food products, enhancing nutritional knowledge among pregnant women at risk of chronic energy deficiency, and strengthening village budget planning and cadre development. These findings highlight the need for targeted interventions to improve program sustainability, particularly in the environmental dimension, to ensure long-term success in reducing stunting prevalence.